2022
DOI: 10.1021/acs.est.2c06211
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Methane Measurements at Oil and Gas Facilities Reveal Necessary Frameworks for Improved Emissions Accounting

Abstract: Methane mitigation from the oil and gas (O&G) sector represents a key near-term global climate action opportunity. Recent legislation in the United States requires updating current methane reporting programs for oil and gas facilities with empirical data. While technological advances have led to improvements in methane emissions measurements and monitoring, the overall effectiveness of mitigation strategies rests on quantifying spatially and temporally varying methane emissions more accurately than the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…30 The amount of emissions reported from this sector can vary widely because of different measurement or estimation techniques and geographical variations. 31 However, important identified sources include storage tanks, equipment leaks, pneumatic controllers, liquids unloading, associated gas flaring and venting, completions and workovers, and methane slip. 32 Additionally, large amounts of CH 4 emissions are attributed to low production well sites, requiring particular attention for further mitigation efforts.…”
Section: Sectoral Emissions Mitigationmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The amount of emissions reported from this sector can vary widely because of different measurement or estimation techniques and geographical variations. 31 However, important identified sources include storage tanks, equipment leaks, pneumatic controllers, liquids unloading, associated gas flaring and venting, completions and workovers, and methane slip. 32 Additionally, large amounts of CH 4 emissions are attributed to low production well sites, requiring particular attention for further mitigation efforts.…”
Section: Sectoral Emissions Mitigationmentioning
confidence: 99%
“…Additional alternatives currently under development consider monitoring networks capable of capturing the characteristic temporal and spatial variabilities of oil and gas CH 4 emissions for detailed emission inventories. 31 In addition, abatement technologies limit loss of valuable, salable natural gas, rendering it a cost-effective mitigation technology. 44…”
Section: Sectoral Emissions Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cusworth et al, sampling a larger number of sites, found that short-lived (<1 month) and long-lived (>1 year) sources were both significant contributors to overall emissions across multimonth and multiyear campaigns. Wang et al also found that for some oil and gas basins, the most common emission duration was <1 h . The variability in emission magnitude and duration requires that a large number of observations be taken to accurately measure and represent these high-emission events.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,13 Bottom-up inventories have been found to underestimate total emissions and are poorly suited to accommodate these complicated emission characteristics. [14][15][16][17][18][19] Therefore, direct measurements are needed to better understand and mitigate emissions. In fact, the Inflation Reduction Act will soon require that all reported methane emissions from the United States oil and gas sector are derived from empirical data rather than conventional bottom-up inventories.…”
mentioning
confidence: 99%